2010
DOI: 10.1007/s10532-010-9353-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Pseudomonas sp. CBW capable of degrading carbendazim

Abstract: With the intensive application of carbendazim in greenhouse production of vegetables and the production of medicinal herbs, there is an increasing need to find a way to remediate carbendazim-contaminated soil. A bacterial stain capable of utilizing carbendazim as the sole source of carbon and energy was isolated from soil. The isolate was designated CBW and identified as a member of Pseudomonas sp. based on its colony morphology, 16S rRNA gene sequencing and Biolog analysis. About 87.1 and 99.1% of carbendazim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 24 publications
1
37
0
1
Order By: Relevance
“…However, the complete degradation pathway of 2-AB is not known. For example, Fang et al (2010) studying the degradation of MBC by Pseudomonas sp. CBW revealed that 2-hydroxybenzimidazole (2-HB) was detected as a metabolite of 2-AB.…”
Section: Dynamics Of Tm Disappearance and Amounts Of Mbc And 2-ab In mentioning
confidence: 99%
“…However, the complete degradation pathway of 2-AB is not known. For example, Fang et al (2010) studying the degradation of MBC by Pseudomonas sp. CBW revealed that 2-hydroxybenzimidazole (2-HB) was detected as a metabolite of 2-AB.…”
Section: Dynamics Of Tm Disappearance and Amounts Of Mbc And 2-ab In mentioning
confidence: 99%
“…As shown in Table 2, the degradation rates of metamitron by the isolate MET at pH 5.0, 7.0, and 9.0 were 0.04, 1.00, and 0.10 mg/l/h, with the corresponding degradation half-lives of 144.4, 1.5, and 52.5 h, respectively, after 9 h of incubation. The results showed that the degradation of metamitron by the isolate MET was significantly ( p  ≤ 0.05) faster at pH 7.0 than at pH 5.0 and 9.0, implying that microbial degradation was a pH-dependent process202122. Similarly, Liu et al 23.…”
Section: Resultsmentioning
confidence: 82%
“…However, this bacterial strain could not remove carbendazim effectively from the mineral salts medium supplemented with higher concentration of carbendazim (100 mg L -1 ), i.e. only 9.9 % carbendazim was degraded after 3-day incubation (Fang et al, 2010). In contrast, Pseudomonas sp.…”
Section: Discussion:-mentioning
confidence: 82%